Comparison among Mainland China, Taiwan and Hong Kong's translated foreign movie titles : a discourse analysis - Ip, Tiffany Zi Yan (2019)
The main objective of the present study was to investigate how the language style and translation style chosen by translators reflect the culture and societal attitudes of the target audience. Translated English film titles from Mainland China, Taiwan and Hong Kong (=HK) were selected for this analysis. The data was compared and analysed based on their semantics and pragmatics in relation to different translation styles/methods and different cultural backgrounds of the regions. Results indicated that China mostly used literal translation with a strong obligation to remain as faithful to the original title as possible. Meanwhile, HK used a high degree of free translation, combined with linguistics puns and colloquialism to adapt to local culture and special consideration was taken to achieve the aesthetic function of titles. Recurring words to enhance sensationalism were also used to reveal plot and thematic elements in the title. Taiwan demonstrated a mix of all translation methods, using more popular culture references instead of colloquial language. HK’s methods could be attributed to strong affirmation to cultural identity, while China’s methods of foreignization could be influenced by strong advocating from local scholars in the 1980s. Chinese scholars believed that domestication could ruin national features of the source culture. Taiwan’s trends could suggest that their local identity is reflected in popular culture items, rather than colloquial dialect. Changing forms of communication and rapid globalization could change translation trends of these regions in the future.